Factors in Teenagers' Decision Making to Become Punk - Aprinal Syah, Anggi; Sugiarto, Arridho; Nurbaniyah, Nurbaniyah (Lafadz Jaya Publisher, 2024)
Salusu (1996:47) defines decision-making as the process of choosing an alternative way of acting using an efficient method according to the situation. Adolescence, derived from the Latin word